The defense industry - Gansler, Jacques S. (Cambridge, Mass. : MIT Press, 1982)
Economic analysis of the defence industry in the USA - examines its industrial structure, economic role, economic implications for market access, cost effectiveness, research and development, etc. Arising from its monopsonistic contracting relationship with the state; points out that the industry is not self-sufficient but dependent on trade; recommends government policy changes to increase both industrial production efficiency and strategic responsiveness; looks at the shipbuilding and aircraft industries in particular. Bibliography and graphs.
Includes bibliographical references (pages 321-330) and index.
Keywords: War -- Economic aspects -- United States; commerce international; United States; USA; economic analysis; bibliography; graph; graphique